Prognostic Significance of Venous Thromboembolic Events in Disseminated Germ Cell Cancer Patients. (26th January 2017) - Gonzalez-Billalabeitia, Enrique; Castellano, Daniel; Sobrevilla, Nora; Guma, Josep; Hervas, David; Luengo, Maria I.; Aparicio, Jorge; Sanchez-Muñoz, Alfonso; Mellado, Begoña; Saenz, Alberto; Valverde, Claudia; Fernandez, Antonio; et al.
Abstract : Background: Disseminated germ cell cancers are at high risk of developing thromboembolic complications. We evaluated the prognostic value of venous thromboembolic events (VTE) in disseminated germ cell cancer. Methods: Patients with germ cell cancer receiving upfront platinum-containing chemotherapy between 2004 and 2014 were pooled from the Spanish Germ Cell Cancer Group (SGCCG) registry and reviewed for the presence of VTE. Results were validated in an independent international group of patients. We used a penalized Cox proportional hazards model including VTE as a time-varying covariate to identify and validate prognostic factors. All statistical tests were two-sided. Results: The SGCCG registry identified 416 patients from 14 referral institutions. With a median follow-up of 49 months, VTEs were observed in 9% of patients (n = 38). Events occurred at diagnosis, during chemotherapy, and after chemotherapy in 2.6%, 5.0%, and 1.4% of patients, respectively. VTE was associated with shorter progression-free survival (PFS; hazard ratio [HR] = 2.29, 95% confidence interval [CI] = 1.18 to 4.47, P = .02) and overall survival (OS; HR = 5.14, 95% CI = 2.22 to 11.88, P < .001). In multivariable analysis, the effect was consistent in the intermediate-risk group, both for PFS (HR = 9.52 95% CI = 2.48 to 36.58, P < .001) and OS (HR = 12.84, 95% CI = 2.01 to 82.02, P = .007). VTE at diagnosis is also an adverse prognostic variable for progression-free survival (HR = 4.64, 95% CI = 2.04 to 10.54, P < .001) and for overall survival (HR = 6.28, 95% CI = 1.68 to 17.10, P = .01). These results were validated in an independent international cohort that included 241 patients from four hospitals. Conclusions: VTE is an independent adverse prognostic factor in disseminated germ cell cancers, in particular for the intermediate prognostic group of the International Germ Cell Cancer Collaborative Group classification. The presence of VTE at diagnosis has also prognostic significance and should be further explored in future prognostic classifications.